Experimental and numerical investigation on the dynamic failure envelope and cracking mechanism of precompressed rock under compression-shear loads - Xu, Y; Pellegrino, A; Dai, F; Du, H (American Society of Civil Engineers, 2021)
The complex response of underground geomaterials subjected to dynamic disturbance arises from the microstructure redistribution under high in- situ stress and the resulting fracture behaviors at multiaxial stress states. Inclined specimens were employed in an axially constrained split Hopkinson pressure bar (SHPB) system to achieve a combination of compression-shear stress states and static-dynamic loads. The loading rate under investigation ranged from 500 to 4,000 GPa/s, along with the axial prestress of 7, 21, 35, 49, and 63 MPa on specimens with an inclination of 0°, 3°, 5°, and 7°. The modified SHPB experimentation and discrete-element method modeling were implemented to unravel the combined effects of the loading rate, preload, and stress path on the failure mechanism of sandstone specimens involving the failure strength and envelope, fracturing pattern, fragmentation, and microcracking process. The positive rate dependence of the failure strength and Drucker-Prager envelope was observed. The preload showed double effects on the failure strength, indicated by an upper bound of the failure envelope as it expanded with the increasing preload. The microdamage accumulated during preloading and the global stress field collectively influenced the failure pattern of the inclined specimen, altering from a shear fracturing mode under dynamic loading or high-preload static-dynamic loading to an axial splitting mode near the specimen surface under low-preload static-dynamic loading.